Auxin regulates anthocyanin biosynthesis through the Aux/IAA–ARF signaling pathway in apple. Issue 1 (December 2018) - Wang, Yi-cheng; Wang, Nan; Xu, Hai-feng; Jiang, Sheng-hui; Fang, Hong-cheng; Su, Meng-yu; Zhang, Zong-ying; Zhang, Tian-liang; Chen, Xue-sen
Abstract Auxin signaling, which is crucial for normal plant growth and development, mainly depends on ARF–Aux/IAA interactions. However, little is known regarding the regulatory effects of auxin signaling on anthocyanin metabolism in apple (Malus domestica ). We investigated the functions of MdARF13, which contains a repression domain and is localized to the nucleus. This protein was observed to interact with the Aux/IAA repressor, MdIAA121, through its C-terminal dimerization domain. Protein degradation experiments proved that MdIAA121 is an unstable protein that is degraded by the 26S proteasome. Additionally, MdIAA121 stability is affected by the application of exogenous auxin. Furthermore, the overexpression ofMdIAA121 andMdARF13 in transgenic red-fleshed apple calli weakened the inhibitory effect of MdARF13 on anthocyanin biosynthesis. These results indicate that the degradation of MdIAA121 induced by auxin treatment can release MdARF13, which acts as a negative regulator of the anthocyanin metabolic pathway. Additionally, yeast two-hybrid, bimolecular fluorescence complementation, and pull-down assays confirmed that MdMYB10 interacts with MdARF13. A subsequent electrophoretic mobility shift assay and yeast one-hybrid assay demonstrated that MdARF13 directly binds to the promoter ofMdDFR, which is an anthocyanin pathway structural gene. Interestingly, chromatin immunoprecipitation–quantitative real-time PCR results indicated that the overexpression ofMdIAA121 clearly inhibits the recruitment of MdARF13 to theMdDFR promoter. Our findings further characterized the mechanism underlying the regulation of anthocyanin biosynthesis via Aux/IAA–ARF signaling. A green light for red apples Insights into a hormonal signaling pathway controlling apple coloration could help growers to consistently produce eye-catching fruit. Auxins are signaling molecules that regulate many important metabolic pathways in plants. Research from a team led by Xue-sen Chen at Shandong Agricultural University in China now reveals how the auxin naphthalene acetic acid (NAA) controls production of anthocyanin, the molecule that gives red apples their distinctive coloration. The researchers determined that increasing NAA levels result in reduced production of anthocyanin. These effects are mediated by a subset of auxin-associated proteins that regulate the expression of genes that contribute to the synthesis of this pigment. The color of fruit can strongly influence consumer purchasing decisions, and this signaling pathway could help horticulturalists to ensure that apples retain their visual appeal even under inclement growing conditions.